A model for tobacco industry in Malaysia - Idris, Nurjihan; Kasron, Norzalila; Ismail, Mohd Mansor; Shamsudin, Mad Nasir; Mohamed Arshad, Fatimah (School of Social Sciences, Universiti Sains Malaysia, 2012)
A study was conducted to analyze the factors affecting the tobacco industry in Malaysia. Tobacco farmers were found to be more concerned with the changes in input particularly, fertilizer. Both incentive scheme for tobacco fertilizer and fertilizer price show significant impact on the area planted as both factors will affect the cost of production. Another significant determinant on supply side is tobacco farm price. Higher price will attract tobacco farmers to be more productive and this will lead to higher yield. On the demand side, the price of cigarette is significant in explaining the changes in tobacco domestic demand. As cigarette price increases, firms will be sensitive towards the price increase and this will reduce the quantity of tobacco consumed by the manufacturers. Lastly, the result shows that import demand for tobacco is income elastic.